Living in solitude or building reefs: ecophenotypic variation of the vermetid Petaloconchus varians revealed by mitochondrial DNA analysis. (18th November 2022) - Breves, André; de Paula, Thiago Silva; Spotorno, Paula; Fernandes, Maurício Romulo; Lôbo-Hajdu, Gisele; Pimenta, Alexandre Dias
Abstract: This study aimed to investigate whether the marine snails Petaloconchus varians (d'Orbigny, 1839) and Petaloconchus myrakeenae Absalão & Rios, 1987 from southeastern Brazil are conspecific. Both species were described from Rio de Janeiro, and they diverge mainly in their growth forms (i.e. gregarious for P. varians and solitary for P. myrakeenae ). Examination of shell features, operculum, radula and anatomic details revealed no differences between the species. Analysis of partial cytochrome c oxidase subunits I (CO1) sequences showed that all Petaloconchus samples from Rio de Janeiro clustered into a single clade, which included specimens from the Caribbean (Venezuela). In addition, a genetic differentiation test showed that the analysed populations are structured and the species likely originated in the Caribbean and has undergone significant population expansion. We conclude that P. myrakeenae is a junior synonym of P. varians and provide a morphological redescription of the latter. Furthermore, we argue that different growth forms of P. varians are ecophenotypes, apparently influenced by wave action and water temperature. Tests should be conducted to confirm this hypothesis and to evaluate the impact of other parameters on the plasticity of growth forms, such as food supply and habitat heterogeneity.